The planetary model as an organizational framework for the generation of innovation - Steiner, Gerald R. (Naše gospodarstvo, 2006)
In this paper the "Planetary Model" is introduced as a meta-model for dealing with the complexity of sustainable innovation. Based on a sociocybernetic point of view, the "Planetary Model" can support innovators and their teams to organize innovation processes for the uncertainty and dynamics of complex innovation problems. Consequently, the importance of creative problem-solving is stressed. These interdependences also lead to a permanently changing pattern. Circularity instead of linearity becomes the determining element. Finally, provocative questions on the ability of science itself to be innovative and deal with complex problems are asked.
Keywords: inovacije; ustvarjalnost; reševanje problemov; sistemi; kompleksni sistemi; teorija sistemov; modeli